PENERAPAN PAIKEM DALAM PROSES PEMBELAJARAN PAK UNTUK MENINGKATKAN MINAT BELAJAR SISWA SMK NEGERI 4 KOTA SORONG PROPINSI PAPUA BARAT - Tia Metanfanuan (Yayasan Akrab Pekanbaru, 2019)
Our education has so far emphasized the cognitive domain, informative knowledge, which only uses traditional learning models or in the direction of the learning process. The PAK field of study is one of the areas of research that is based on building and forming individuals, as well as the growth of the faith of students. As educators who are directly related to the teaching and learning process, the teacher will play an essential role in determining the learning outcomes that students will achieve. The selection of the right learning model is a demand and must be fulfilled by an educator so that the process of delivering material or learning material can arouse students' learning interest, the results of which will determine the achievements that students will achieve. The approach of this research is quantitative research with a correlational approach, which is to find out how much influence PAIKEM has on the PAK teaching and learning process on increasing student interest in learning. The results of this study are the magnitude of the influence of the PAIKEM model on student learning interest is 0.998 with a Very Strong interpretation and has a relationship with a value of 0.733. So as an educator who is directly related to the teaching and learning process plays an essential role in determining student learning outcomes, for that the teacher must change the old teaching pattern by using the PAIKEM model to increase students' interest in learning.